PENGARUH SUHU DAN LAMA PENYANGRAIAN DENGAN OVEN DRIER TERHADAP KARAKTERISTIK TEH BERAS MERAH JATILUWIH - Utami Dewi, Ni Luh Putu Diyan; Wrasiati, Luh Putu; Anom Yuarini, Dewa Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
This research aimed to 1) determine the effect of temperature and roasting time with oven drier on the characteristics of red rice tea 2) get the temperature and optimal roasting time to produce red rice tea with the best characteristics. This study used a factorial Randomized Block Design with 2 factors. The first factor roasting which consists of 3 levels : 140°C, 165°C and 190°C. The second factor is roasting time, which consists of 4 levels : 5, 10, 15 and 20 minutes. Observed variables in this research include water content, ash content, crude fiber content, juice content, anthocyanin content, antioxidant activity and organoleptic. The results showed that temperature and roasting time having effect on water content, crude fiber content, antocyanin content, antioxidant activity, scoring color, and scoring aroma of red rice tea but no effect on ash content, juice content, scoring flavor and overall acceptance of red rice tea Jatiluwih. Interaction temperature and rosting time having effect on water content, crude fiber content, antioxidant activity but no effect on ash content, juice content, and anthocyanin content. Higher temperature and longer roasting time, levels of anthocyanins, the antioxidant activity and water content will decrease. Drying temperature of 140°C with 5 minute roasting time is the best treatment to produce the characteristic red rice tea Jatiluwih. The characteristics of water content 2,11%, ash content 1,21%, crude fiber content 1,28%, juice content 19,87%, anthocyanin content 0,52 mg/L, antioxidant activity 18,34 mgGAE/L, scoring colour of red rice tea 3,20 (between pink to red), scoring flavor of red rice tea 3,40 (between the usual flavors to taste somewhat astringent), scoring aroma of red rice tea 2,67 (between the typical aroma of red rice to red rice rather typical aroma), and the overall acceptance of red rice tea 4,87 (between neutral to not like). Keyword : red rice tea, temperature, time, roasting
Keywords: 92,